Peran Bidang Kedokteran dan Kesehatan Kepolisian dalam Penegakan Hukum terhadap Kasus Penyalahgunaan Narkotika: Perspektif Hukum Kesehatan - Mirwan Siagian; Herlina Hanum Harahap (Jurnal Begawan Hukum (JBH), 2025)
The abuse of narcotics in Indonesia has become a serious threat to public health and social order. In supporting law enforcement efforts against narcotics abuse cases, the role of the Police Medical and Health Division (Biddokkes) is crucial. Biddokkes is not only responsible for conducting medical and forensic examinations on suspects but also plays a key role in assessment and rehabilitation recommendations for drug addicts. The health law approach, which emphasizes recovery and the protection of human rights, serves as a vital framework in addressing these cases. This study aims to analyze the role of Biddokkes in supporting law enforcement processes against narcotics abuse and to examine how health law can be applied in this context. The research uses a normative-empirical method with primary and secondary data obtained through document studies, interviews, and field observations within Biddokkes of the North Sumatra Regional Police. The results show that Biddokkes plays a strategic role in legal proceedings, including conducting medical examinations, issuing visum et repertum, toxicology testing, and clinical assessments that determine the legal status of suspects. The findings also indicate that medical examination results from Biddokkes serve as vital evidence in court and form the basis for recommending rehabilitation for drug users. However, challenges such as limited facilities, human resources, and pressure in forensic practices remain obstacles. Therefore, the integration of criminal law and health law approaches must be continuously strengthened to establish a fair, humane, and recovery-based legal enforcement system.